Effect of air gap in the performance of AGMD system - Perves Bappy, Mohammad Jabed; Bahar, Rubina; Ariff, Tasnim Firdaus (Asian Research Publishing Network (ARPN), 2016)
Air Gap Membrane distillation (AGMD) is a prominent technology in the field of water treatment and desalination which is facing a lot of challenges to efficiently produce pure water supply. The system works under the principle of partial pressure difference created between a hydrophobic membrane and a coolant plate by varying temperature on both sides. The membrane and the coolant plate are separated by a thin air gap. Impure hot water flows over the membrane and the evaporated vapour is allowed to pass through the hydrophobic membrane only. Later this vapour condensed on the coolant plate and the pre distilled water is collected. Among the various factors affecting the performance of AGMD system, width of the air gap is the major one to consider. The target of this article is to understand the effect of air gap in AGMD system which will help to build an efficient AGMD water supply system in future using appropriate air gap. In this paper, heat and mass transfer process through the air gap has been discussed for AGMD and a numerical investigation was performed using ANSYS Fluent 15.0 software package and compared with previous experimental results. The investigation shows that distillate flux increased with the decrease of air gap width where the highest 96% of increase of distillate flux found when the air gap is decreased 2.5mm